Post-Post-Kemalism, One More Time: Criticisms, Responses, Reflections - İlker Aytürk (European Journal of Turkish Studies)
This article is an attempt at stocktaking five years after the publication of the 2015 article on post-Kemalism. It also responds to critics, who filled two consecutive issues of the journal Birikim, as part of a special dossier on the post-Kemalist paradigm.